Some trematodes including three new species from freshwater fishes of Venezuela - Moravec, Frantisek; Prouza, Antonin (Folia parasitologica, 2024)
The present paper comprises a systematic survey of trematodes found in 13 species of freshwater fishes in Venezuela collected in 1992, 1996 and 2001. The following 15 trematode species were recorded: Adults: Genarchella venezuelaensis sp. n., Thometrema dissimilis sp. n., Megacoelium spinicavum Thatcher et Varella, 1981, Doradamphistoma bacuense Thatcher, 1999, Crassicutis cichlasomae Manter, 1936, Parspina carapo Ostrowski de Núñez, Arredonto et Gil de Pertierra, 2011, Phyllodistomoides hoplerythrini sp. n. Larvae (metacercariae): Clinostomatopsis sorbens (Braun, 1899), Clinostomum marginatum (Rudolphi, 1819), C. detruncatum Braun, 1899, Ithyoclinostomum dimorphum (Diesing, 1850), Odhneriotrema microcephala (Travassos, 1922), Tylodelphys sp., Posthodiplostomum sp., Sphincterodiplostomum sp. All these parasites are reported from Venezuela for the first time and many of these findings represent new host records. The new species G. venezuelaensis sp. n., T. dissimilis sp. n. and P. hoplerythrini sp. n. were collected from the accessory respiratory organ of Loricariichthys brunneus (Hancock) (Loricariidae), from the stomach of Hoplerythrinus unitaeniatus (Spix et Agassiz) (Erythrinidae) and from the intestine of H. unitaeniatus, respectively. All parasites are briefly described and illustrated and problems concerning their morphology, taxonomy, hosts and geographical distribution are discussed. Megacoelium spinispecum Thatcher et Varella, 1981 is considered a junior synonym of M. spinicavum Thatcher et Varella, 1981, and Crassicutis opisthoseminis Bravo-Hollis et Arroyo, 1962 as a junior synonym of C. cichlasomae Manter, 1936.
Keywords: Animals; Trematoda; paraziti; infekce červy třídy Trematoda; Trematode Infections; taxonomy; Venezuela; nemoci ryb; Fish Diseases; Fishes; Neotropical Region; ryby; Parasites; Fresh Water; sumci; Catfishes; Plathelminthes; sladká voda; helminth parasites; zvířata; Pisces; Characiformes